Exportaciones del Perú y el APEC desde una perspectiva de la dotación de factores - Ormeño, Arturo (2003)
Because of the structural reforms of the first years of the nineties, Peru has managed to reverse the declining trend of exports observed during the second half of the eighties. In addition, in 1998 it has joined APEC, a fact that represents a set of possibilities for the development of the commercial exchange. This article seeks to identify what type of products have benefited from this process of reforms and which will depend, with greater intensity, on the development of current potentialities. Likewise, it is about establishing what productive factors explain these results. To do this, econometric estimations are made, based on a model of the extended Hecksher-Ohlin type, to a sample of APEC countries. The results indicate that although factors such as the stock of capital, the geographical area and the availability of land for cultivation and forestry activity are significant to explain the dynamics of exports, there are others in which the government can directly influence, such as the degree of openness and the educational level of the population.